2007
DOI: 10.1016/j.ijheatmasstransfer.2006.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Permeability and effective thermal conductivity of bisized porous media

Abstract: In the region of minimum porosity of particulate binary mixtures, heat exchange and permeability were found to be higher than the ones obtained with a mono-size packing built with the same small size particles used in the binary packing. This effect was noticed in the range of the particles size ratio 0.1-1.0.The obtained improvement on thermal performance is related to the increase of effective thermal conductivity (ETC) in the binary packing and to the increase in transversal thermal dispersion due to the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 22 publications
1
22
0
1
Order By: Relevance
“…1), approached the experimental values for mono-size glass beads packing and a binary packing formed by a mixture of glass beads with size ratio d = d/D = 0.333/ 1.179 = 0.282 at x D = 0.7 (Dias et al, 2004b;Dias et al, 2007;Mota et al, 2001). This particle size ratio is close to the one used in the experiments below with the binary packing, d = 0.263.…”
Section: Determination Of Column Cooling Lengthsupporting
confidence: 70%
See 3 more Smart Citations
“…1), approached the experimental values for mono-size glass beads packing and a binary packing formed by a mixture of glass beads with size ratio d = d/D = 0.333/ 1.179 = 0.282 at x D = 0.7 (Dias et al, 2004b;Dias et al, 2007;Mota et al, 2001). This particle size ratio is close to the one used in the experiments below with the binary packing, d = 0.263.…”
Section: Determination Of Column Cooling Lengthsupporting
confidence: 70%
“…Obtained result means that for a 200-mm column, which was the one used in this work, the non-isothermal flow occupies only 10% of the total column length. Furthermore (Dias et al, 2007), as is shown in Fig. 3, heat transfer will be improved with a column filled with a binary packing.…”
Section: Determination Of Column Cooling Lengthmentioning
confidence: 95%
See 2 more Smart Citations
“…[2][3][4][5] and many references therein. The structural properties of packings are intimately related to certain macroscopic properties of granular matter such as sound propagation, 6 thermal conductivity, 7 permeability, 8 reactivity, 9 tensile strength, 9 dilation 10 and others. Of particular recent interest is the relationship of the microstructure of packings in the jammed state and the process of jamming in granular dynamics, e.g.…”
Section: Introductionmentioning
confidence: 99%